Pengelolaan arsip sebagai penunjang penilaian akreditasi Program Studi Pendidikan Islam Anak Usia Dini (PIAUD) IAIN Sultan Amai Gorontalo - Laila Mada; Taufik Taib (Al-Kuttab : Jurnal Kajian Perpustakaan, Informasi dan Kearsipan, 2023)
Archives have an important role in providing information to users in making decisions. The management of archives in the Early Childhood Islamic Education (PIAUD) study program cannot be separated from the accreditation activities that have been periodically determined by the National Accreditation Board for Higher Education (BAN-PT). Form accreditation documents are often slumped and the archives are irregular which must be arranged, causing the Study Program Management Unit (UPPS) to have difficulty organizing and archiving the required documents. The results of the research on the Early Childhood Islamic Education (PIAUD) study program show that some archive management activities have been carried out well and some have not been carried out properly. Records management for accreditation purposes that has been carried out by the study program plays an important role because it can facilitate, expedite, and shorten the time in recovering archives when needed by either the form filling team or the assessor team.